The Effect of Water Intake during Pregnancy on Birth Weight: Pengaruh Asupan Air selama Kehamilan pada Berat Lahir Bayi - Tria Rosemiarti; Hardinsyah Hardinsyah; Sudung O. Pardede; Parlindungan Siregar; Budi I. Santoso; Netta M. Putri; Ratu S. Hanifah (Indonesian Journal of Obstetrics and Gynecology, 2023)
AbstractObjective: This systematic review aimed to investigate theeffect of water intake during pregnancy on infant birthweight.Methods: A comprehensive search was conducted usingthe keywords "water intake," "dehydration," "pregnancy,""outcome," "hydration," "birth weight," and "birth outcome"in databases such as "SCOPUS," "EBSCO," "PUBMED,""COCHRANE," and through "Google Search." MeSH headings"pregnancy" and "hydration" were used for the search.Inclusion criteria encompassed pregnant women withoutpathological disorders, birth weight as a studied outcome,prospective cohorts, clinical trial study designs, and Englishlanguagepapers. Out of the 254 articles retrieved, six metthe specifi ed requirements and were included in this review.Results: The fi ndings from the six studies consistentlydemonstrated a positive correlation between higher waterintake, improved hydration, and increased birth weight.All studies measured water consumption or hydrationstatus between 8-37 weeks of gestation. Regardless of theduration of the studies, underhydration or low water intakewas consistently associated with lower birth weight.Conclusion: This review highlights that increasing waterintake among pregnant women positively affects infantbirth weight. Adequate water intake during pregnancy isrecommended to be in the range of 2180 – 3000 mL daily,considering hydration status and the stage of pregnancy.Keywords: birth weight, hydration, pregnancy, water intake.AbstrakTujuan: Untuk mengungkap pengaruh asupan air selamakehamilan terhadap berat lahir bayi.Metode: Menggunakan kata kunci “water intake,""dehydration," "pregnancy," "outcome," "hydration," "birthweight," dan "birth outcome,", artikel dicari. Data diambil daridatabase "SCOPUS," "EBSCO," "PUBMED," "COCHRANE,"dan "Google Search". Kami menggunakan MeSH headingskehamilan dan hidrasi untuk istilah pencarian. Kriteria inklusiadalah perempuan hamil tanpa kelainan patologis, beratbadan lahir adalah salah satu luaran penelitian, desain studiberupa kohort prospektif dan uji klinis, serta artikel dalambahasa Inggris. Dari 254 artikel yang diperoleh, enam artikelmemenuhi persyaratan dan digunakan untuk review ini.Hasil: Dari keenam penelitian menunjukkan bahwa semakintinggi asupan air, semakin baik hidrasi atau asupan airmeningkatkan berat bayi lahir. Semua penelitian mengukurkonsumsi air atau status hidrasi antara 8-37 minggu. Studistudiini secara konsisten memberikan bukti bahwa asupanair yang rendah atau kondisi kekurangan cairan dikaitkandengan berat badan lahir rendah, terlepas dari durasi studi.Kesimpulan: Kajian ini menunjukkan bahwa peningkatanasupan air ibu hamil berpengaruh positif terhadap beratlahir bayi. Asupan air yang cukup pada ibu hamil adalah2180 – 3000 mL setiap hari bergantung pada status hidrasidan usia kehamilan.Kata kunci: asupan air, berat lahir, hidrasi, kehamilan.